Digital Receipts for a Greener Future: Web-Based Innovation in Toll Payment Systems - Asriani; Mashuri Said; Ahmed H. Arnous (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2025)
This study presents the implementation of a web-based digital receipt system in the transaction processes of PT. Makassar Metro Network and PT. Jalan Tol is a strategic response to operational challenges during the COVID-19 pandemic. The reliance on printed receipts led to increased operational expenses and issues in receipt management, including frequent loss and negative environmental impact. To address these issues, a web-based application was developed to facilitate access to digital receipts, aiming to reduce the use of thermal paper and improve cost efficiency. The research adopts the System Development Life Cycle (SDLC) methodology using the Waterfall model, which encompasses stages of planning, requirements analysis, system design, implementation, and maintenance. Testing results indicate that all application features functioned as intended, enhancing both accessibility and transaction efficiency. These outcomes suggest that digital receipts can significantly reduce environmental footprints and streamline operational workflows. Furthermore, the developed model offers potential for broader adoption across various industries seeking sustainable and digital transaction solutions. The integration of digital receipts thus emerges as a viable, eco-friendly alternative in the modernization of toll payment systems.